Instructional Designers’ Perceptions of Accessible and Inclusive Online Course Design - Lomellini, Amy; Lowenthal, Patrick R; Trespalacios, Jesús; Snelson, Chareen (Online Learning, 2024)
As online learning in higher education expands, institutions are challenged to meet the needs of diverse students. COVID has further emphasized the need for inclusive online course design for all learners, especially those with disabilities. We interviewed instructional designers about their perceptions, knowledge, and responsibilities in accessible and inclusive online course design. Results indicated that instructional designers play a critical role in advocating and advancing initiatives related to designing accessible and inclusive online learning experiences. Participants described a desire for increased support and resources to help facilitate an institutional culture shift toward proactive course design strategies.